2017
DOI: 10.1590/1516-4446-2016-2007
|View full text |Cite
|
Sign up to set email alerts
|

Chronotype and anxiety are associated in patients with chronic primary insomnia

Abstract: Objective: To assess the interaction of chronotype with anxiety in patients with chronic primary insomnia. Methods: Sixty-four patients (50 women) with mean age 43.968.1 years were investigated with the Horne and Ö stberg Morningness-Eveningness Questionnaire (MEQ) and State-Trait Anxiety Inventory (STAI). Results: Significant negative correlations of chronotype-MEQ score with STAI state-anxiety (r = -0.40, p o 0.05), STAI trait-anxiety (r = -0.40, p o 0.05), and STAI pre-sleep state anxiety (r = -0.30, p o 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 5 publications
2
9
0
1
Order By: Relevance
“…In the present study, the evening chronotype was associated with higher trait and anxiety states and worse sleep quality. Previous studies have shown results in the same direction regarding the relationship between chronotypes and sleep quality [47][48][49][50][51][52] and anxiety state/trait [30]. Passos and collaborators (2017) reported an association between chronotypes and anxiety in a population of patients with primary chronic insomnia.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…In the present study, the evening chronotype was associated with higher trait and anxiety states and worse sleep quality. Previous studies have shown results in the same direction regarding the relationship between chronotypes and sleep quality [47][48][49][50][51][52] and anxiety state/trait [30]. Passos and collaborators (2017) reported an association between chronotypes and anxiety in a population of patients with primary chronic insomnia.…”
Section: Discussionmentioning
confidence: 74%
“…Recent studies suggest that chronotype may also be an important marker of the origin of chronic primary insomnia, a risk factor for anxiety disorders [30]. It is also possible to point out a relationship between morningness and performance in high school students [31].…”
Section: Introductionmentioning
confidence: 99%
“…The circadian preference or the athletes' chronotype was evaluated by the of the Horne and Östberg´s Questionnaire, 16 composed by 19 self-evaluating questions on which the individual must register his preferential times in routine situations of the daily life. Scores above 58 classify individuals as morning persons, below 42 as afternoon persons and from 42 to 58, as intermediate or indifferent persons.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast with DoA studies, the relationship between circadian rhythmicity, sleep-wake disorders and chronotype has been widely explored in psychiatric disorders [ 82 , 83 , 84 ]. Circadian rhythm disruption and the evening chronotype have been associated with bipolar disorder and depression and anxiety scales [ 84 , 85 ]. Subjects with DoA, compared with healthy controls, also report higher scores in depression and anxiety questionnaires [ 86 ], together with the presence of a possible history of traumatic events [ 87 ].…”
Section: Circadian Rhythm and Chronotypementioning
confidence: 99%